2020
DOI: 10.1111/bjd.19509
|View full text |Cite
|
Sign up to set email alerts
|

A head‐to‐head comparison of ixekizumab vs. guselkumab in patients with moderate‐to‐severe plaque psoriasis: 24‐week efficacy and safety results from a randomized, double‐blinded trial*

Abstract: Summary Background Significantly more patients with moderate‐to‐severe plaque psoriasis treated with the interleukin (IL)‐17A inhibitor ixekizumab vs. the IL‐23p19 inhibitor guselkumab in the IXORA‐R head‐to‐head trial achieved 100% improvement in Psoriasis Area and Severity Index (PASI 100) at week 12. Objectives To compare skin and nail clearance and patient‐reported outcomes for ixekizumab vs. guselkumab, up to week 24. Methods IXORA‐R enrolled adults with moderate‐to‐severe plaque psoriasis, defined as sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 25 publications
2
80
0
10
Order By: Relevance
“…Seven studies included comparative data (two placebo-controlled trials (9,14) and five head-to-head active-comparator trials (7,11,13,15,16)) on week 24-26 outcomes that connected to form an evidence network comparing seven interventions (Figure 1). Examination of DIC indicated that the fixed-effect model was more suitable to fit the data, although results for the random-effect model were similar.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Seven studies included comparative data (two placebo-controlled trials (9,14) and five head-to-head active-comparator trials (7,11,13,15,16)) on week 24-26 outcomes that connected to form an evidence network comparing seven interventions (Figure 1). Examination of DIC indicated that the fixed-effect model was more suitable to fit the data, although results for the random-effect model were similar.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, it is possible that drug-and class-specific differences exist, given the micro-anatomical link between NP and psoriatic arthritis (30,31) in combination with the differential treatment effects of the various drug classes on psoriatic arthritis (1)(2)(3)(4)(5)18). This is, for instance, exemplified by the comparable effect of ixekizumab and guselkumab on skin clearance but not on nail clearance at week 24 in the IXORA-R trial (13). Even though for many biologics improvement in NP continues until 52 weeks of continuous treatment (7)(8)(9)(10)(11), it remains to be seen whether this discrepancy in the clearance rates of NP between these two drugs remains.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations